(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, the author outlined all the components of a healthy lifestyle in philosophy. A healthy lifestyle is an individual system of human behavior that provides him with physical, mental and social well-being in the real environment (natural, man-made and social) and active longevity.